Massive pulmonary embolism and thrombophilia - Qureshi, Iman (BMJ Publishing Group, 2013)
A 32-year-old man presented overnight to the accident and emergency unit with mild breathlessness on exertion. He was found to be hypoxic on room air and his chest x-ray revealed areas of patchy lung consolidation. He was given intravenous antibiotics for presumed community-acquired pneumonia. Unfortunately his condition deteriorated and he remained significantly hypoxic despite high-flow oxygen with ECG evidence of right heart strain. Further questioning revealed a history of protein S deficiency and a strong family history of venous thromboembolic disease. An urgent CT pulmonary angiogram showed an evidence of massive pulmonary embolism and the patient was successfully thrombolysed.